Response of varieties of elephant foot yam (Amorphophallus paeoniifolius) to organic management - SUJA, G; JYOTHI, A N; BYJU, G (The Indian Journal of Agricultural Sciences, 2016)
Consumer awareness regarding the impacts of high-input chemical intensive conventional agriculture on the soil, environment and human health has spurred the growth of organic agriculture systems. Organic agriculture ensures sustainable production, safe food and environmental conservation. It is estimated that more than 95% of organic production is based on crop varieties that were bred for the conventional high-input sector. Such varieties lack important traits required under organic and low-input production conditions. There is dearth of information on the response of varieties to organic management. Field experiments were conducted for two years during 2010 and 2011 at the Central Tuber Crops Research Institute, Thiruvananthapuram, to compare the growth, yield and quality performance of five elephant foot yam [Amorphallus paeoniifolius (Dennst.) Nicolson] varieties (Peerumade local, Gajendra, Sree Padma, Vegetable and Fruit Promotion Council Keralam (VFPCK) local and Sree Athira) and soil physicochemical and biological properties under organic vs conventional systems in split plot design. Varieties Ã— production systems interaction was not significant for most of the variables. The elite as well as the local varieties responded equally well to both the systems with average corm yields of 27.72 tonnes/ha under organic and 28.55 tonnes/ha under conventional practice. The var. Gajendra responded well to organic management producing higher yield (+10%). The other varieties had lower yield losses (-2.5-15.0%) under the organic system. The corms of the varieties had slightly higher dry matter, sugar, P, K and Fe contents under organic system. The varieties also exerted similar effects on soil physicochemical and biological properties, when tested under organic and conventional management. However, Gajendra and Sree Padma effected significantly higher organic C status under organic management due to greater biomass addition on account of their innate robust plant type. In general, there was significant improvement in soil pH and bacterial count, slight lowering of bulk density and particle density, improvement in water holding capacity, secondary and micronutrient status, N fixers and dehydrogenase enzyme activity in the organic system.